"It Felt Like Violence": Indigenous Knowledge Traditions and the Postcolonial Ethics of Academic Inquiry and Community Engagement. Issue 3 (20th September 2017) - Gone, Joseph P.
Highlights: Research approaches based on Indigenous epistemologies are called Indigenous Research Methodologies. Consideration of IRMs evoked a thorny ethical challenge concerning publicization of sacred knowledge. This ethical challenge resists resolution owing to competing values promoted by community psychology. Abstract: In a 2014 presentation at an academic conference featuring an American Indian community audience, I critically engaged the assumptions and commitments of Indigenous Research Methodologies. These methodologies have been described as approaches and procedures for conducting research that stem from long‐subjugated Indigenous epistemologies (or "ways of knowing"). In my presentation, I described a Crow Indian religious tradition known as a skull medicine as an example of an indigenous way of knowing, referring to a historical photograph of a skull medicine bundle depicted on an accompanying slide. This occasioned consternation among many in attendance, some of whom later asserted that it was unethical for me to have presented this information because of Indigenous cultural proscriptions against publicizing sacred knowledge and photographing sacred objects. This ethical challenge depends on enduring religious sensibilities in Northern Plains Indian communities, as embedded within a postcolonial political critique concerning the accession of sacred objects by Euro‐American collectors during the early 20th century. I complicate these ethical claims by considering competing goods that are valued by community psychologists, ultimately acknowledging that the associated ethical challenge resists resolution in terms that would be acceptable to diverse constituencies.